Creep Behavior of Saturated Clay in Triaxial Test and a Hyperbolic Model. (16th November 2021) - Xiao, Bin; Hu, Minyun; Zhou, Peijiao; Lu, Yuke; Zhang, Yong
Abstract : As one of the basic mechanical properties of soil, the creep property of a given type soil is related to stress path, and stress level. In this paper, triaxial shear creep tests under different deviatoric stress levels were performed on both intact sample and the reconstituted sample of clay taken from Hangzhou, China. Based on the Boltzmann linear superposition principle, the creep curves of the clay sample under different levels of deviatoric stress were obtained, and the creep characteristics of the intact sample and the reconstituted sample were compared in both total stress creep analysis and effective stress creep analysis. Furthermore, the creep curves were fitted using a hyperbolic creep model. The results show that (1) under the same stress level, the creep of intact sample evolves more than that of reconstituted sample; (2) the hyperbolic creep model is suited to describe the creep characteristics of intact and reconstituted clay, and the model parameters A s and B s can be linearly correlated to the stress level D r ; (3) for the application of the hyperbolic model, the total stress analysis works better, and the model parameters A s and B s can be determined by a linear relationship with Dr.